2009
DOI: 10.1021/la8043347
|View full text |Cite
|
Sign up to set email alerts
|

c(4 × 2) Structures of Alkanethiol Monolayers on Au (111) Compatible with the Constraint of Dense Packing

Abstract: Using alkanethiol dense packing as a starting point, we have found six prototypical packing structures commensurate with the (3x2 radical3) supercell of the Au (111) surface. Five of the six structures are not compatible with the flat surface conditions but can be fitted to a reconstructed surface. Combined with density functional theory calculations and simulations of grazing incidence X-ray diffraction maps and of scanning tunneling microscopy images, this allowed us to refine and assess the recently propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…We note that the results from the core-level spectroscopy conform to the energetic argument in the preference for the MeS-Au-SMe structure over alternative adsorption models. 22 It is also consistent with experimental STM, 23 IR, 24 GIXRD, 25 and NEXAFS ͑Ref. 26͒ data.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We note that the results from the core-level spectroscopy conform to the energetic argument in the preference for the MeS-Au-SMe structure over alternative adsorption models. 22 It is also consistent with experimental STM, 23 IR, 24 GIXRD, 25 and NEXAFS ͑Ref. 26͒ data.…”
Section: Discussionsupporting
confidence: 78%
“…22 Although there is an uncertainty concerning the ability of state-of-the-art DFT methods to predict small energy differences ͓in particular, for reconstructed RS / Au͑111͒ systems, as the cohesive energy of gold is underestimated by ϳ15%͔ the structure based on RS-Au-RS units is consistent with the bulk of experimental data. RS-Au-SR complexes bonded to Au͑111͒ has been observed at different coverages by STM, 23 calculations of the infrared ͑IR͒ vibrational signatures match the experimental data, 24 simulations of the GIXRD maps 25 are in agreement with experiments and calculations for the RS-Au-RS structure compare favorably with sulfur K-edge near-edge x-ray absorption fine-structure ͑NEXAFS͒ measurement. 26 It has also been suggested that the RS-Au-RS structure might be consistent with normal-incidence XSW data.…”
Section: Introductionsupporting
confidence: 72%
“…[10][11][12][13][14][15]. These potential applications of SAMs of thiols on gold surface motivate many researchers to explore the nature of adsorbed species, site of adsorption and the nature of interaction between adsorbed species and the gold surface using experimental and theoretical investigations [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Earlier experimental and theoretical report suggested that the SAMs of methylthiol preferred to adopt a (H3 9 H3)R30°s tructure and may manifest c(2 9 4) superstructure upon varying the chain length; the S head group seems to predominately attack the fcc (face-centered cubic) site of Au (111) surface [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…All DFT calculations used the Amsterdam Density Functional (ADF) 2010.01 program (41,42). A slab of gold having the bulk structure was passivated in four sites on the (111) surface with either methylamine or ethylthiolate (43,44). C and H atom positions were initially relaxed using the UFF as implemented in the Avogadro 1.1.0 software (45).…”
mentioning
confidence: 99%